Demonstration of a picosecond Bragg switch for hard X‐rays in a synchrotron‐based pump–probe experiment. (12th June 2019) - Sander, Mathias; Bauer, Roman; Kabanova, Victoria; Levantino, Matteo; Wulff, Michael; Pfuetzenreuter, Daniel; Schwarzkopf, Jutta; Gaal, Peter
Abstract : A benchmark experiment that demonstrates the shortening of hard X‐ray pulses in a synchrotron‐based optical pump–X‐ray probe measurement is reported. Abstract : A benchmark experiment is reported that demonstrates the shortening of hard X‐ray pulses in a synchrotron‐based optical pump–X‐ray probe measurement. The pulse‐shortening device is a photoacoustic Bragg switch that reduces the temporal resolution of an incident X‐ray pulse to approximately 7.5 ps. The Bragg switch is employed to monitor propagating sound waves in nanometer thin epitaxial films. From the experimental data, the pulse duration, diffraction efficiency and switching contrast of the device can be inferred. A detailed efficiency analysis shows that the switch can deliver up to 10 9 photons s −1 in high‐repetition‐rate synchrotron experiments.